Boundary extension is attenuated in patients with ventromedial prefrontal cortex damage. (November 2018) - De Luca, Flavia; McCormick, Cornelia; Mullally, Sinead L.; Intraub, Helene; Maguire, Eleanor A.; Ciaramelli, Elisa
Abstract: The ventromedial prefrontal cortex (vmPFC) and hippocampus have been implicated in the mental construction of scenes and events. However, little is known about their specific contributions to these cognitive functions. Boundary extension (BE) is a robust indicator of fast, automatic, and implicit scene construction. BE occurs when individuals who are viewing scenes automatically imagine what might be beyond the view, and consequently later misremember having seen a greater expanse of the scene. Patients with hippocampal damage show attenuated BE because of their scene construction impairment. In the current study, we administered BE tasks to patients with vmPFC damage, brain-damaged control patients, and healthy control participants. We also contrasted the performance of these patients to the previously-published data from patients with hippocampal lesions (Mullally, Intraub, & Maguire, 2012). We found that vmPFC-damaged patients showed reduced BE compared to brain-damaged and healthy controls. Indeed, BE attenuation was similar following vmPFC or hippocampal damage. Notably, however, whereas hippocampal damage seems to particularly impair the spatial coherence of scenes, vmPFC damage leads to a difficulty constructing scenes in a broader sense, with the prediction of what should be in a scene, and the monitoring or integration of the scene elements being particularly compromised. We conclude that vmPFC and hippocampus play important and complementary roles in scene construction.